USM-INSTITUT TEKNOLOGI BANDUNG TO COLLABORATE IN MICROELECTRONICS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, June 2015 Universiti Sains Malaysia (USM) has recently extended its strategic cooperation with Institut Teknologi Bandung (ITB), one of the leading institutions in Indonesia, to jointly develop capacity of both institutions especially in the field of Microelectronic Engineering.